(untitled) (Journal of Human Sciences, 2023)
The COVID-19 pandemic resulted in the closure of schools and universities, disrupting the education of nearly 1.6 billion students globally. The sudden transition from traditional face-to-face classes to online instruction was particularly challenging for developing countries like Libya, where educational institutions lacked the necessary digital tools and students had limited access to devices and reliable internet. In response, the higher education system in Libya scrambled to meet the technology needs to facilitate distance education. This case study, focusing on the University of Benghazi, examines the shift to entirely online teaching and learning, highlighting the experiences gained by faculty members during the crisis and evaluating ways to improve distance learning and remote training for professors and students. The study also provides recommendations for academic institutions to quickly shift to an online learning modality, if needed, and evolve their curriculum to offer appropriate online courses.